The Emerging Roles of Endoplasmic Reticulum Stress in Balancing Immunity and Tolerance in Health and Diseases: Mechanisms and Opportunities - Li, Anqi; Song, No-Joon; Riesenberg, Brian P.; Li, Zihai (Frontiers in Immunology, 2020)
The endoplasmic reticulum (ER) is an organelle equipped with mechanisms for proper protein folding, trafficking and degradation to maintain protein homeostasis in the secretory pathway. As a defense mechanism, perturbation of ER proteostasis by ER stress agents activates a cascade of signaling pathways from the ER to the nucleus known as unfolded protein response (UPR). The primary goal of UPR is to induce transcriptional and translational programs to restore ER homeostasis for cell survival. As such, defects in UPR signaling have been implicated as a key contributor to multiple diseases including metabolic diseases, degenerative diseases, inflammatory disorders and cancer. Growing evidences support critical role of ER stress in regulating the fate as well as the magnitude of the immune response. Moreover, the availability of multiple UPR pharmacological inhibitors raises the hope that targeting UPR can be a new strategy for immune modulation and immunotherapy of diseases. This paper reviews the principal mechanisms by which ER stress affects immune cell biology and function, with a focus of discussion on UPR-associated immunopathology and the development of potential ER stress-targeted therapeutics.